2010
DOI: 10.1021/jp908309f
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Triblock Copolymers for Dispersion of Individual, Pristine, Single-Walled Carbon Nanotubes in Organic Solvents

Abstract: Triblock copolymers, polyethylene oxide-(hexa-p-phenylene)-polyethylene oxide, were synthesized and used for dispersing single-walled carbon nanotubes (SWNT) in organic solvents. The resulting dispersions comprise mostly of individual tubes, as indicated by transmission electron microscopy at cryogenic temperatures. The dispersions could be dried and redispersed by the addition of a solvent, offering a useful method of application of predispersed SWNT. In situ optical spectroscopy indicates that the block copo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Nevertheless, the prevailing effect among the two is still under investigation. Polyethylene glycol (PEG) chains with PEG repeating units as long as 8, have been demonstrated [ 52 ] to favor both self-assembly and dispersion of SWCNTs in chloroform and 1,2-dichlorobenzene once chosen a hydrophobic domain B (i.e., hexa- p -phenylene) able to establish π–π interactions with the B block of another monomer or with the SWCNT surface, respectively. On the other hand, the capability of polystyrene- b -polyisoprene (PS- b -PI) diblock copolymers to disperse MWCNTs seems to be dominated by the solvent selectivity of the block copolymers, being the direct interaction between the nanotubes and the polymers of secondary importance [ 53 ].…”
Section: Reviewmentioning
confidence: 99%
“…Nevertheless, the prevailing effect among the two is still under investigation. Polyethylene glycol (PEG) chains with PEG repeating units as long as 8, have been demonstrated [ 52 ] to favor both self-assembly and dispersion of SWCNTs in chloroform and 1,2-dichlorobenzene once chosen a hydrophobic domain B (i.e., hexa- p -phenylene) able to establish π–π interactions with the B block of another monomer or with the SWCNT surface, respectively. On the other hand, the capability of polystyrene- b -polyisoprene (PS- b -PI) diblock copolymers to disperse MWCNTs seems to be dominated by the solvent selectivity of the block copolymers, being the direct interaction between the nanotubes and the polymers of secondary importance [ 53 ].…”
Section: Reviewmentioning
confidence: 99%
“…It was shown that tri‐block copolymers that contain a middle block comprising a conjugated polymer and two non‐conjugated tails (for example ref …”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…At this inter‐tube separation, the attractive interaction between adjacent tubes is much smaller than k B T (see Fig. (d)), and thus the weak‐long ranged repulsion prevents aggregation of the individually dispersed tubes …”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…The furfuryl groups are designed to react with maleimide groups in polymaleimides through a Diels–Alder (DA) reaction to form thermally labile cross-linked networks, while the pyrene groups physically anchor to the surface of carbon materials through π–π interactions. As a proof-of-concept, multiwalled carbon nanotubes (CNTs) were chosen as a model nanomaterial to investigate our rMDBC stabilization strategy. CNTs have outstanding optical, electrical, and thermal properties. The synthesis and use of MDBCs with pendant aromatic moieties to disperse carbon materials, including CNTs, in solutions have been described in several reports; however, the rMDBC stabilization of CNT surfaces is rarely explored. As illustrated in Figure , the rMDBC enabled the stabilization of CNT surfaces to form colloidally stable rMDBC/CNT colloids.…”
Section: Introductionmentioning
confidence: 99%